FILOSOFI RAK-RAK, RIK-RIK, RUK-RUK SUKU BADUY DAN RELEVANSINYA TERHADAP PENDIDIKAN KARAKTER SISWA SD - Novita Fatmasari; Anisah; Ujang Jamaludin; Ila Rosmilawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study discusses the philosophy of "Rak-rak, Rik-rik, Ruk-ruk" in the life of the Baduy Tribe and its relevance to the character education of elementary school students. The three philosophies describe the stages of life that emphasize hard work in youth, living simply and saving as a form of future readiness, and enjoying old age without burdening others. These values are not only the guideline for the life of the Baduy people, but also reflect local wisdom that is inherited from generation to generation through examples, habits, and daily life practices. The research was conducted with a descriptive qualitative approach through interviews with former jaro, Baduy youth, housewives, and a researcher who understood Baduy customs. The results of the study show that the application of this philosophy appears to be strong in the daily activities of the community, ranging from agricultural activities, weaving, mutual cooperation, to the way they manage natural resources and families. The process of internalizing values takes place naturally in the living room, social environment, and customs that are consistently maintained. The findings of the study show that the philosophy of Rak-rak, Rik-rik, and Ruk-ruk has significant relevance to 18 values of character education in elementary school, such as discipline, hard work, independence, honesty, social care, and care for the environment. These values can be integrated into learning through teacher example, habituation, contextual learning, and school-to-family collaboration. Thus, the local wisdom of Baduy becomes a source of character education that is concrete, contextual, and easy to apply in the daily lives of students.